The Effect of 1,2,4-Triazole-3-thiol Derivatives Bearing Hydrazone Moiety on Cancer Cell Migration and Growth of Melanoma, Breast, and Pancreatic Cancer Spheroids - Aida Šermukšnytė; Kristina Kantminienė; Ilona Jonuškienė; Ingrida Tumosienė; Vilma Petrikaitė (MDPI AG, 2022)
4-Phenyl-3-[2-(phenylamino)ethyl]-1H-1,2,4-triazole-5(4H)-thione was used as a starting compound for the synthesis of the corresponding 1,2,4-triazol-3-ylthioacetohydrazide, which reacts with isatins and various aldehydes bearing aromatic and heterocyclic moieties provided target hydrazones. Their cytotoxicity was tested by the MTT assay against human melanoma IGR39, human triple-negative breast cancer (MDA-MB-231), and pancreatic carcinoma (Panc-1) cell lines. The selectivity of compounds towards cancer cells was also studied. In general, the synthesized compounds were more cytotoxic against the melanoma cell line. N'-(2-oxoindolin-3-ylidene)-2-((4-phenyl-5-(2-(phenylamino)ethyl)-4H-1,2,4-triazol-3-yl)thio)acetohydrazide, N'-((1H-pyrrol-2-yl)methylene)-2-((4-phenyl-5-(2-(phenylamino)ethyl)-4H-1,2,4-triazol-3-yl)thio)acetohydrazide and N'-(2-hydroxy-5-nitrobenzylidene)-2-((4-phenyl-5-(2-(phenylamino)ethyl)-4H-1,2,4-triazol-3-yl)thio)acetohydrazide were identified as the most active among all synthesized compounds in 3D cell cultures. N'-(4-(dimethylamino)benzylidene)-2-((4-phenyl-5-(2-(phenylamino)ethyl)-4H-1,2,4-triazol-3-yl)thio)acetohydrazide inhibited all cancer cell migration, was characterized as relatively more selective towards cancer cells, and could be further tested as an antimetastatic candidate.